Chapter 9 EU External Action, Intention and Explanation - de Zwart, Frank (Taylor & Francis, 2019)
""Unintended consequences" is an umbrella concept. It comprises phenomena that differ in crucial respects and consequently, without refinement, it remains a rather blunt instrument for policy analysis. The contributions in this volume, however, show that disentangling unintended consequences by making clear distinctions between various types, makes the concept much more useful for policy analysis. Assessing the impact of EU foreign policies as studied in this volume, we show that "bonuses", "windfalls", "accidents", and "trade-offs" - all unintended - are very different when it comes to the explanation of policy outcomes, or to allocating responsibility for them."